The Problem of Psycho Correction in Pedagogical Activity (Journal of Pedagogical Inventions and Practices, 2022)
The article discusses the principle of unity of diagnosis and correction. Diagnostics not only precedes psychological impact, but also serves as a means of monitoring changes in personality, emotional states, behavior, and cognitive functions during correctional work, as well as a tool for evaluating it.